From Farm to Town: The Changing Pattern of Textile Production in Anglo-Saxon England - Penelope Walton Rogers (Fasciculi Archaeologiae Historicae, 2018)
Through much of the Anglo-Saxon period (the 5th to 11th centuries AD), textile production was a farm-based, rural industry. The middle period, however, saw the appearance of some large estate centres, producing high quality goods for an elite group, and small overseas trading centres through which surplus cloths may have been channelled. As towns began to emerge in the 9th century, opportunities for regional and overseas trade increased. Textile production in Late Anglo-Saxon towns can be seen as a phase of social and economic change, as a supply network for raw materials was established. By this means, foundations were laid for both urban gilds and the English cloth export trade of later centuries.